(untitled) (El-Wahat Journal for Research and Studies, 2021)
Electronic espionage is considered one of the most serious crimes that threaten the security of individuals and it threatens the security and economy of countries. Therefore, Islamic law has addressed this traditional and modern danger. The law also addresses the most important penalties that may be imposed on those who penetrate systems, tampering with databases, By programs and viruses specializing in this aspect, which we will explain in this research. Keywords: Encryption, Sensitivity, Eavesdropping, Breakthrough, Viruses.